The legality of advance directives in Malaysia from the medical law perspective - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (2015)
Over the past century, the health care industry has witnessed a strong deference to the principle of patient autonomy. The greater focus on a patient’s right to self-determination which is concomitant with the decline in medical paternalism is attributable to several factors, including rapid technological advancements in medicine and the increase in medical awareness as a result of patients gaining easier access to medical information. Accordingly, advance directives have emerged as a response to the fear that many people have over the fact that in this day and age, it has become medically possible to continuously be kept “alive” in a state where they have lost all cognitive functions and are incapable of exercising any control over how they wish to be treated. An advance directive serves as an assurance that the right of an individual to make autonomous decisions will not be defeated by any future incapacity, and thus in this respect, functions as an enhancement of patient autonomy.